2020
DOI: 10.3847/1538-4357/ab711f
|View full text |Cite
|
Sign up to set email alerts
|

Radio/X-Ray Correlation in the Mini-outbursts of Black Hole X-Ray Transient GRS 1739–278

Abstract: We present quasi-simultaneous radio and X-ray observations of the black hole X-ray binary GRS 1739-278 of its 2015-2016 mini-outbursts, i.e. between 2015 June 10 and 2016 October 31, with the X-ray-to-radio time interval being less than one day. The monitor campaign was run by Swift in the X-rays and by JVLA in the radio (at both 5 GHz and 8 GHz). We find that the brightest radio emission is actually achieved during the soft sate, and the spectrum is marginally optically-thick with the spectral index α ≈ −0.28… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…For the mini-outburst with a lower accretion rate, the viscosity parameter is very small (e.g., α ∼ 0.01, Xie and Yuan, 2016). With the accretion rate decaying, the electron density and the magnetic strength increases, which can result in the increasing of synchrotron absorption depth in luminous hot accretion flow and thereby leading to softer X-ray spectra (e.g., Yang et al, 2015;Xie and Yuan, 2016;Xie et al, 2020). We will obtain a negative Ŵ−F X correlation.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For the mini-outburst with a lower accretion rate, the viscosity parameter is very small (e.g., α ∼ 0.01, Xie and Yuan, 2016). With the accretion rate decaying, the electron density and the magnetic strength increases, which can result in the increasing of synchrotron absorption depth in luminous hot accretion flow and thereby leading to softer X-ray spectra (e.g., Yang et al, 2015;Xie and Yuan, 2016;Xie et al, 2020). We will obtain a negative Ŵ−F X correlation.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…The unusual outbursts have been found where XRBs are either still in the LHs or transition into the IMs before return to the LHs or quiescent state (e.g., Capitanio et al, 2009;Del Santo et al, 2016), which are often called a mini-outburst. In recent years, more and more mini-outbursts have been observed in several BH XRBs (e.g., GRS 1739-278, GX339-4, H1743-322, Swift J1753.5-0127, V404 Cyg, Capitanio et al, 2009;Munoz-Darias et al, 2016;Plotkin et al, 2017;Yan and Yu, 2017;Garcia et al, 2019;Xie et al, 2020), neutron star (NS) XRBs (e.g., XTE J1701-407 Degenaar et al, 2011), and even WZ sge type dwarf novae (DN) (e.g., Kato et al, 2004). However, the nature of minioutburst is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This model is applied to the three mini-outbursts of XTE J1550-564 by [39]. Xie et al [40] studied the 2015-2016 mini-outbursts of GRS 1739-278. They found that the radio spectral index of the mini-outbursts is 0.28 ± 0.17 with JVLA (Karl G. Jansky Very Large Array) and observed a flat radio-X-ray correlation with µ ∼ 0.16.…”
Section: Unstable Inner Disk/discrete Accretionmentioning
confidence: 99%
“…Such behaviour is similar to the two tracks observed in main outbursts. The physical reason may be that the slope (the q in Equation ( 4)) of η/ε changes with accretion rates in mini-outbursts, where the mini-outbursts may suffer lower viscous parameter α as suggested in [40], as α controls the critical accretion rate (and luminosity) of different accretion models.…”
Section: Unstable Inner Disk/discrete Accretionmentioning
confidence: 99%
“…This model is applied to the three mini-outbursts of XTE J1550-564 by [39]. Xie et al [40] studied the 2015-2016 mini-outbursts of GRS 1739-278. They found that the radio spectral index of the mini-outbursts is 0.28 ± 0.17 with JVLA (Karl G. Jansky Very Large Array) and observed a flat radio-X-ray correlation with µ∼0.…”
Section: Unstable Inner Disk/discrete Accretionmentioning
confidence: 99%